Prevalence of injuries associated with High Rise Syndrome in cats presented to the University Veterinary Hospital (UVH), Universiti Putra Malaysia - Ab Rahman, Muhammad Dzul Ikraam (2015)
The identification of common High Rise Syndrome (HRS) injuries in cats may help to fill the information gap required to prevent and treat the injuries. The prevalence of the 21 injuries, three most common injuries, and the correlation between height of fall and severity of injuries were determined in this study. Logbooks and medical cases of cats presented to the UVH, UPM from 1 January 2002 until 31 December 2014 were reviewed. The criteria used for selected cases were cats diagnosed with HRS, fell from at least the 2nd storey, had diagnostic imaging findings, and must have at least one out of the 21 injuries associated with HRS in this study. The prevalence of injuries associated with HRS in this study were limb fractures (60%) (12/20), pneumothorax (30%) (6/20), epistaxis and vertebral luxation (20%) (4/20) each, wound, haematuria, and limb luxation (15%) (3/20) each, and laceration, pulmonary contusion, dental fractures, hard palate fractures, pelvic fractures, and vertebral fractures (5%) (1/20) each. Three most common injuries associated with HRS were limb fractures, pneumothorax, and epistaxis; the fourth injury, vertebral luxation, shared the same prevalence with epistaxis. The height of fall at 3rd to 6th storeys was positively and moderately correlated with the severity of injuries of cats with HRS (r=0.622; p=0.031; n=12).